The risk of sexual dysfunction associated with alcohol consumption in women: a systematic review and meta-analysis - Salari, Nader; Hasheminezhad, Razie; Almasi, Afshin; Hemmati, Mahvan; Shohaimi, Shamarina; Akbari, Hakimeh; Mohammadi, Masoud (Springer Science and Business Media LLC, 2023)
Background: Alcohol abuse among women is a significant health problem. Consuming alcohol in high amounts causes decreased sexual stimulation, vaginal lubrication, dyspareunia, and difficulty reaching orgasm. Due to the different effects of alcohol consumption on sexual function, this study aimed to investigate the effect of alcohol consumption on sexual dysfunction in women. Methods: In this study, the researchers conducted a systematic search of several databases, including PubMed, Google Scholar, Scopus, Web of Science, Embase, and ScienceDirect, as well as the Google Scholar search engine, to identify studies reporting the impact of alcohol consumption on female sexual dysfunction. The search was conducted up until July 2022. A total of 225 articles were searched in the databases, and an additional 10 relevant articles were identified through manual search. After removing 93 articles due to duplication, 90 articles were excluded based on the study's inclusion and exclusion criteria. During the merit evaluation phase, 26 articles were excluded through the full-text study based on the study’s inclusion and exclusion criteria, while 26 articles were excluded due to their low quality. Ultimately, only 7 studies were deemed suitable for the final evaluation. The analysis was conducted using a random effects model, while the heterogeneity of the studies was assessed using the I2 index. Data analysis was performed using the Comprehensive Meta-Analysis Version 2 software. Results: Based on the review of 7 studies involving a total sample size of 50,225 women and using the random effects method, the calculated odds ratio was 1.74 (95% CI: 1.006–3.04). This indicates that alcohol consumption increases the likelihood of sexual dysfunction in women by 74%. The Begg and Mazumdar rank correlation test, was used to analyze the distribution bias, but the results were not significant at the 0.1 significance level (p = 0.763). Conclusion: The findings of this study demonstrate a significant correlation between alcohol consumption and an increased risk of sexual dysfunction in women. These results highlight the need for policymakers to prioritize this issue and raise awareness regarding the harmful effects of alcohol consumption on female sexual function and its impact on population health and reproduction. © 2023, The Author(s).